IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI BUDAYA 5S (SENYUM, SAPA, SALAM, SOPAN, SANTUN) - Fransiska Silvia Novinda Anggraini; Azhar Haq; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
In order to implement good character education in students, educational institutions should apply the culture of MI Bustanul Ulum. The goal is to habituate the character expected by the MI Bustanul Ulum . MI Bustanul Ulum culture and character education must at least go hand in hand in shaping the character of students. This research was conducted at Madrasah Ibtidaiyah Bustanul ulum Kota batu on cempaka street no. 25 Pesanggrahan. This study uses a qualitative approach, where the data obtained is based on the results of observations, interviews and documentation. The results of this study indicate that principals and MI Bustanul Ulum residents actively participate in implementing character education through 5S culture (smile, say to hello, greetings, polite, manners) and character education in this madrasah characterized by a dynamic and positive value through habituation that starts from the smallest thing so participants students become good individuals.Keywords: Character building, Cultural madrasah, Cultural 5S (smile, say to hello, greetings, polite, manners).